Pengaruh Penggunaan Shopeepaylater terhadap Keputusan Belanja Mahasiswa pada E-Commerce Shopee di Universitas Muhammadiyah Kalianda: Penelitian - Fitrah Octavia Riyanti (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This study aims to determine the effect of the use of the Shopee PayLater feature on shopping decisions both partially and simultaneously. This study uses a quantitative research method, the data collection method uses a questionnaire distributed to ShopeePaylater feature users, the population in this study is an unknown number of ShopeePaylater feature users, and sampling in the study uses the Purposive sampling method, the number of samples in this study is 96 respondents, the instrument test uses a validity test, reliability test, and classical assumption test, the analysis in this study uses multiple linear regression. The results of this study indicate that: (H1) The t-count value of 15.674> t-table 1.661 means that the use of the ShopeePaylater feature (X) has a positive and significant effect on shopping decisions. (H2) The F-count value of 245.689> F-table 2.70 means that the use of ShopeePaylater simultaneously has a positive and significant effect on shopping decisions for Shopee consumers at Muhammadiyah University of Kalianda. The conclusion of this study is as follows: the use of the Shopee PayLater feature, both partially and simultaneously, has a positive and significant effect on shopping decisions for Shopee consumers at Muhammadiyah University of Kalianda.